Abundance and distribution of species in relation to soil properties in sedge-dominated habitats in Uyo Metropolis, Southern Nigeria - Mbong EO; Osu SR; Uboh DG; Ekpo I (Global Journal of Ecology - Peertechz Publications, 2020)
A field research was conducted to assess abundance and distribution of species in relation to soil properties in Sedge-dominated Habitats in Uyo Metropolis, Southern Nigeria Systematic sampling method was used. The result of the study revealed that a total of 12 plant species of which 3 were members of the family Cyperaceae were identified in the habitats studied. The Cyperaceae members found were of the genus: Cyperus. Other associated species found were Sida acuta, Scoparia dulcis, Chromolaena odorata, Eleusine indica, Ludwigia decurens etc. The highest density values obtained in this study is characteristic of Cyperus iria in Habitat 4 (9500 st/ha) while the least density value is characteristic of Plastostoma africanum in Habitat 2 (200st/ha). Multivariate correlation and regression techniques evidenced that these differences in density of the sedges reflected the functions of various important soil properties such as pH, exchangeable Ca, soil moisture, total nitrogen and available phosphorus. Most specifically, the current result concludes that Cyperus iria showed strong affinity for alkaline soils rich in calcium while Cyperus difformis and Cyperus rotundus showed strong preference for acid soils. Cyperus difformis, Cyperus rotundus and Cyperus haspan flourished in soils rich in organic manure while Cyperus iria colonies were found thrived on soils with limiting levels of phosphorus This result lends knowledge and practical application in environmental management, weed science and habitat ecology.